Intent to Invest in Cryptocurrency Amid Uncertainty : A Theory of Planned Behavior Approach - Khilar, Ruchi Priya; Singh, Shikta (Indian Journal of Finance, 2025)
Purpose : Investors sometimes have difficulties in making appropriate decisions during unpredictable times such as the COVID-19 pandemic. Based on the extended theory of planned behavior (TPB), the objective of this study was to validate the psychological antecedents of willingness to invest in cryptocurrency during the outbreak of the COVID - 19 pandemic. Design/Methodology/Approach : This study was conducted by collecting primary data from 204 respondents using a structured online questionnaire, which was further analyzed using SPSS Amos 23.0. The current research explored the association between variables named “subjective norms,” “perceived self-efficacy,” and “attitude to invest.” Findings : The findings suggested that “subjective norms” and “perceived self-efficacy” are the major factors influencing investors’ attitudes toward cryptocurrency investment, directly impacting their intentions for the same. The pandemic underscored the dual nature of cryptocurrencies, demonstrating advantages such as enabling remote transactions and providing a hedge against economic instability, while simultaneously displaying difficulties, including environmental implications and market volatility. Practical Implications : The results have important reference significance for future investors who intend to invest in the crypto-assets market. The findings of the study provided important insights to investors and financial planners on which psychological factors affect whether to make a cryptocurrency investment during volatile periods, such as the COVID-19 era. Learning these key aspects will provide scientists with tools to navigate choppy waters, which will ultimately make them better decision-makers. Originality : This research enhanced the existing body of knowledge by uniquely incorporating the extended theory of planned behavior into the context of cryptocurrency investments during a global crisis. It offered an extensive comprehension of investor psychology during periods of uncertainty, essential for both scholarly study and pragmatic investment strategies.